2014
DOI: 10.1002/eji.201444646
|View full text |Cite
|
Sign up to set email alerts
|

Antigen presenting cell‐derived IL‐6 restricts Th2‐cell differentiation

Abstract: The identification of DC-derived signals orchestrating activation of Th1 and Th17 immune responses has advanced our understanding on how these inflammatory responses develop. However, whether specific signals delivered by DCs also participate in the regulation of Th2 immune responses remains largely unknown. In this study, we show that administration of antigen-loaded, IL-6-deficient DCs to naïve mice induced an exacerbated Th2 response, characterized by the differentiation of GATA-3-expressing T lymphocytes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 56 publications
4
23
0
Order By: Relevance
“…We previously reported that this vaccination protocol leads to the coordinated upregulation of Tfh, Th1, Th2, and Th17 responses (19, 20). Analysis of the CD4 + T cell response further confirmed the defect in Tfh cell differentiation despite normal accumulation of CD4 + Ki67 + cells in c-Maf KO-T mice (Figures 4A–F,J).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that this vaccination protocol leads to the coordinated upregulation of Tfh, Th1, Th2, and Th17 responses (19, 20). Analysis of the CD4 + T cell response further confirmed the defect in Tfh cell differentiation despite normal accumulation of CD4 + Ki67 + cells in c-Maf KO-T mice (Figures 4A–F,J).…”
Section: Resultsmentioning
confidence: 99%
“…Although we did not explore the underlying mechanism, we note that (1) IL-6 activation of IL-6R inhibits LPS-induced dendritic cell maturation in vivo 51 and (2) dendritic cells produce IL-6, which inhibits CD4 1 T H 2 cell differentiation both in vivo and in vitro. 52 Blockade of IL-6R would relieve these inhibitory effects of IL-6 and therefore prolong or exacerbate the immune response to allergen challenge. This would be consistent with the predicted inhibition of IL-6 classic signaling conferred by the IL6R allele (rs2228145:C) that increases asthma risk.…”
Section: Discussionmentioning
confidence: 99%
“…The Th-2 cells also mediate reactions to allergens. The most potent antigen-presenting cells, the dendritic cells (DCs), secrete IL-6 and inhibit the differentiation of T cells towards the Th-2 phenotype, suggesting that IL-6 plays a dominant negative role in Th-2-cell development [6].…”
Section: Biological Effects Of Il-6 In Immunitymentioning
confidence: 99%